Penerapan Teknik Dramatik Peran Sosial Tokoh Utama Cerpen “Hawa Panas” : Kolaborasi Mahasiswa Prodi Pendidikan Bahasa dan Sastra Indonesia dan Matematika - Imelda Oliva Wissang; Bernardus Bin Frans Resi; Irwanius Piter Muaraya; Karolina Letek Karhi; Kristina Beto Nama (Pusat Riset dan Inovasi Nasional, 2026)
The activity to discover the social role of the main character in the short story Hawa Panas by Silvester Petara Hurit was carried out using a qualitative method with dramatic techniques. This method directly explains the concrete actions carried out by the characters in the story. This activity integrates a sociological approach to literature and mathematical concepts to explain the social roles that appear in the story. The collaboration between the Indonesian Language and Literature Education study program and the Mathematics Education study program at the FKIP Larantuka Teacher Training and Technology Institute allows the application of mathematical concepts in understanding the story. In this short story, there are several social roles that can be found, namely: (1) building relationships between individuals to create strong social bonds, (2) being sensitive in responding to surrounding conditions and providing appropriate responses, (3) communicating appropriately to avoid misinterpretation, (4) using a cultural approach to respect prevailing social norms, and (5) showing compassion for others. This activity also provides a deeper understanding of the application of social concepts in everyday life through literary stories.